Mediation in Germany and Other Western Countries - KURY, HELMUT; KUHLMANN, ANNETTE (Kriminologijos studijos, 2017)
Empirical studies over the past decades have repeatedly shown the limited usefulness of harsh punishment in reducing crime. In response to these research results, historical approaches to crime reduction, such as mediation and restorative justice, have regained prominence, especially in Germany and other western European countries. The women’s movement and the growing role of victimology have contributed to the increased use of these methods as alternatives to incarceration. The debates across these countries vary depending on the historical background of the penal climate in these states, which particularly explains the differences between Eastern and Western European countries in this regard. Empirical studies show the positive impact of mediation on offenders as well as victims. Yet in spite of these results, in most countries, including Germany, the use of mediation remains limited, especially in regard to adult offenders. At the same time, the uses of mediation in non-criminal conflict settings, such as schools, family or work disputes have increased significantly with positive results.
Keywords: Victim-Offender-mediation; Penal climate; Punitiveness; Restitution; Effects of empirical research on alternative penal reactions